2016
DOI: 10.1186/s12864-016-3222-0
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome sequencing and gene expression profiling of Elymus nutans under cold stress

Abstract: Background Elymus nutans Griseb., is an important alpine perennial forage of Pooideae subfamily with strong inherited cold tolerance. To get a deeper insight into its molecular mechanisms of cold tolerance, we compared the transcriptome profiling by RNA-Seq in two genotypes of Elymus nutans Griseb. the tolerant Damxung (DX) and the sensitive Gannan (GN) under cold stress.ResultsThe new E. nutans transcriptomes were assembled and comprised 200,520 and 181,331 transcripts in DX and GN, respectively. Among them, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 70 publications
(86 reference statements)
2
37
0
Order By: Relevance
“…4). Under cold stress, carbohydrates can act as osmotic protectants to stabilize cell membranes and remove ROS, thereby protecting plants from oxidative damage [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…4). Under cold stress, carbohydrates can act as osmotic protectants to stabilize cell membranes and remove ROS, thereby protecting plants from oxidative damage [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggested that our P. sibirica EST dataset provided a more adequate transcriptome resource for cold-responsive gene discovery and functional analysis in conifer species. It has also been demonstrated that cold resistance can be enhanced in plants by gene induction and repression in response to cold stress [22,23]. Some of the P. sibirica DEGs had no annotated homologs in the public database, which indicated that these DEGs might be speci c to P. sibirica or that the coldresponsive genes with homologs have not been identi ed in previous studies with other plant species.…”
Section: Discussionmentioning
confidence: 99%
“…The gene related to the activity of chlorophyllase activity was repressed in P. sibirica. The photochemical reaction of photosynthesis comprises two optical systems, PS I and PS II, which play a decisive role in the photosynthetic capacity of plants [23]. The genes encoding photosystem II reaction center X protein (PsbX) and Photosystem I reaction center subunit VI-2 were downregulated in P. sibirica in response to cold stress.…”
Section: Photosynthesis Under Cold Stressmentioning
confidence: 99%
“…The sequences of the DEGs were aligned to the KEGG database using BLASTX, retrieving proteins with the highest sequence similarity with the given sequences along with functional annotations for their proteins [74][75][76]. Gene ontology (GO) annotations of the DEGs were obtained using the Blast2GO program [74,77].…”
Section: Functional Annotation and Classi Cation Of Degsmentioning
confidence: 99%